Developing Biliary Atresia-like Model by Treating Human Liver Organoids with Polyinosinic:Polycytidylic Acid (Poly (I:C)) - Patrick Ho-Yu Chung; Rosana Ottakandathil Babu; Zhongluan Wu; Kenneth Kak-Yuen Wong; Paul Kwong-Hang Tam; Vincent Chi-Hang Lui (Current Issues in Molecular Biology, 2022)
Background: We explored the feasibility of creating BA-like organoids by treating human liver organoids with Polyinosinic:Polycytidylic acid (Poly I:C). Methods: Organoids were developed from the liver parenchyma collected during Kasai portoenterostomy (BA) and surgery for other liver disorders (non-BA). The non-BA organoids were co-cultured with poly I:C (40 µg/mL). The organoid morphology from both samples was compared on day 17. RNA-sequencing was performed to examine the transcriptomic differences. Results: Non-BA liver organoids developed into well-expanded spherical organoids with a single-cell layer of epithelial cells and a single vacuole inside. After poly I:C treatment, the majority of these organoids developed into an aberrant morphology with a high index of similarity to BA organoids which are multi-vacuoled and/or unexpanded. RNA-sequencing analysis revealed that 19 inflammatory genes were commonly expressed in both groups. Conditional cluster analysis revealed several genes (SOCS6, SOCS6.1, ARAF, CAMK2G, GNA1C, ITGA2, PRKACA, PTEN) that are involved in immune-mediated signaling pathway had a distinct pattern of expression in the poly I:C treated organoids. This resembled the expression pattern in BA organoids (p < 0.05). Conclusions: Poly I:C treated human liver organoids exhibit morphology and genetic signature highly compatible to organoids developed from BA liver samples. They are potential research materials to study immune-mediated inflammation in BA.